Solvent‐free Synthesis of Flowable Carbon Clusters with Customizable Size and Tunable Optical Performance. Issue 12 (4th November 2013) - Li, Denian; Li, Qi; Hu, Xuan; Huang, Jing; Li, Hairong; Dong, Lijie; Xie, Haian; Xiong, Chuanxi
Abstract We propose a rapid and solvent‐free route for synthesizing luminous carbon clusters by controlling carbonization of polyethylene glycol (PEG). This approach does not involve solvents yet uses the precursor itself as suspending medium, thus features mild and green chemistry, and also enables the formation of uniform‐sized carbon clusters, of which the diameter can be easily tuned from 0.7 to 3.5 nm via control of reaction time. In term of the dimension, the resultants are denoted as sub‐nano carbon clusters (SNCs) and carbon dots (CDs), respectively. Benefiting from surface anchored PEG segments, both of the two show favorable flowability at room temperature and excellent solubility in aqueous and organic solvents. Comparison of their optical performances and structures reveals that they share the same chromophores. Particularly, the SNCs demonstrate robust photo‐ and pH‐stable photoluminescence and can be directly applied to cell‐imaging regarding to its prominent biocompatibility. Moreover, its quantum yield (5.5%), which is approximately 3 times higher than that of CDs (1.5%), can be dramatically enhanced to 18.8% by facile chemical reduction. We anticipate that these PEG derivatives marked with easy synthesis, controllable optical performances and excellent physical properties will be highly appealing in future applications.